Avaliação clínica, laboratorial e anatopatológica do sistema urinário de ovinos confinados com e sem suplementação de cloreto de amônio - Santarosa, Bianca Paola [UNESP] (2015)
The incidence of urolithiasis is high in sheep raising, especially in males raised under intensive management. The urinary acidification with ammonium chloride is an effective method to prevent this disease. The objectives of this study with feedlot lambs getting concentrated diet with high protein content, supplemented or not with ammonium chloride, were to verify the effect of diet fed in confinement, rich in concentrated on the formation of uroliths and development of urolithiasis; analyzing the macroscopic and histopathological characteristics of the urinary system; relate the clinical findings, laboratory tests of renal function (urea and creatinine) and necropsy in the presence of uroliths. It was used 60 male sheep, crossbred Ile de France X White Dorper, three to four months old, randomly divided into two groups: Group I (n=40) received 400 mg/kg of ammonium chroride/animal/day orally, for 42 consecutive days; Group II (n=20) was not treated with ammonium chloride. The diet consisted of 85% concentrate, 15% hay, mineral salt and water ad libitum. Moments (M) for clinical evaluation and collection of blood for measurement of serum urea and creatinine were determined as M0, immediately prior to the beginning of the experiment and at intervals of seven days in moments M1, M2, M3, M4, M5 and M6, totaling 56 days of confinement. After the confinement period, the animals were sacrificed, necropsy was performed and their urinary systems were collected for macroscopic and microscopic examination. The animals were observed daily throughout the experimental period, but no animal showed symptoms of obstructive urolithiasis. The values of serum creatinine concentration were below the standard of normality and the values of urea remained above it. Microcalculus were found in the renal pelvis of five animals in both groups. In addition, other changes were found, such as congestion of the renal medullary region and hydronephrosis. The ...